OLAHAN RUMPUT LAUT DI PULAU POTERAN - Isdiantoni Isdiantoni; Ika Fatmawati; Sayyida Sayyida (LPPM Universitas Wiraraja Sumenep, Jalan Raya Sumenep Pamekasan KM. 5 Patean Sumenep 69451, Telp. (0328) 673399 Fax. (0328) 673088, 2018)
Island Poteran one of the islands in Sumenep regency which has significant potential in the fisheries sector. In the year 2013, seaweed production amounted to 58027.61 kg with a value of 97,969,555 rupiah annually. But the use of seaweed in Pulau Poteran far only sold in fresh form. Though there are lots of processed plant that has a high sales value so that it can provide value added The products that can be produced very diverse as seaweed ready though, jellies, candied kelp, and nata de seaweed. Total production is minimal and dependent on demand. Such products cannot penetrate the supermarket because there is no food safety certificate from the ministry of health and the consent of the industry. Packaging products do not meet food safety standards. Through the science and technology to the Community on KWT Putri Tani and KWT Permata District of Talango, then the outcomes expected are as follows: (1) skilled for on KWT Putri Tani and KWT Permata District of Talango in making jelly, candied and nata de seaweed in attractive packaging, (2) the resulting product is the product of jelly, candied and nata de seaweed in beautiful packaging (marketable), (3) Increased sales jelly, candied and nata de seaweed. KWT members apresiasif response and confident enough. The positive reaction was apparent from the members to continue the business of processed plant for domestic industry. After members of the training, participants are motivated to produce and begin to be marketed in the neighborhood. The production of nata de seaweed, dodol and sweets in a sale at some stores around the island Poteran and part of Sumenep.